Aesculus hippocastanum extract and the main bioactive constituent β-escin as antivirals agents against coronaviruses, including SARS-CoV-2 - Peñaranda Figueredo, Freddy Armando (2024)
Respiratory viruses can cause life-threatening illnesses. The focus of treatment is on supportive therapies and direct antivirals. However, antivirals may cause resistance by exerting selective pressure. Modulating the host response has emerged as a viable therapeutic approach for treating respiratory infections. Additionally, considering the probable future respiratory virus outbreaks emphasizes the need for broad-spectrum therapies to be prepared for the next pandemics. One of the principal bioactive constituents found in the seed extract of Aesculus hippocastanum L. (AH) is β-escin. The clinical therapeutic role of β-escin and AH has been associated with their anti-inflammatory effects. Regarding their mechanism of action, we and others have shown that β-escin and AH affect NF-κB signaling. Furthermore, we have reported the virucidal and broad-spectrum antiviral properties of β-escin and AH against enveloped viruses such as RSV, in vitro and in vivo. In this study, we demonstrate that β-escin and AH have antiviral and virucidal activities against SARS-CoV-2 and CCoV, revealing broad-spectrum antiviral activity against coronaviruses. Likewise, they exhibited NF-κB and cytokine modulating activities in epithelial and macrophage cell lines infected with coronaviruses in vitro. Hence, β-escin and AH are promising broad-spectrum antiviral, immunomodulatory, and virucidal drugs against coronaviruses and respiratory viruses, including SARS-CoV-2.